ENSURING FOOD SAFETY – A REQUIREMENT OF THE TIME. - N.Kh. Kobilova; Olimova Komila (Ustozlar uchun, 2025)
Food security is one of the most urgent challenges facing countries around the world. Today, the world needs to radically change its approach to food production and distribution.